Component and antibacterial activity of crystal fraction from Zingiber zerumbetessential oil - Sri Mulyani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
The aims of the study was to determine of the crystal fraction from Zingiber zerumbet essential oils. The components examination was performed by GC-MS method using the solvent n-hexane and anti bacterial activity was tested against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 35218 using agar diffusion method with coconut oil solvent. The components that can be identified are α-humulene, caryophyllene oxide, β-selinene, and zerumbone. Crystal fraction solution able to inhibit of S. aureusATCC 25923 at the concentration 25 % and up to 50 % has not been able to inhibit E. coli ATCC 35218.Key words : Zingiber zerumbet, Lempuyang gajah, Crystal fraction, anti-bacterial